2010
DOI: 10.17221/183/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 11 microsatellite loci for their use in paternity testing in Yugoslav Pied cattle (YU Simmental cattle)

Abstract: Eleven microsatellite loci (TGLA227, BM2113, TGLA53, ETH10, SPS115, TGLA126, TGLA122, INRA023, ETH3, ETH225, BM1824) were evaluated for their use in paternity testing in the Yugoslav Pied cattle (YU Simmental cattle) population in Serbia. A total of 40 animals were tested. At the 11 tested loci, a total of 91 alleles were detected. The mean number of alleles per locus was 8.273. Polymorphism information content (PIC) values ranged from 0.58 to 0.88 with the mean value of 0.72. The most informative loci were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
6
25
0
1
Order By: Relevance
“…By using the same 7 [29] and 11 markers [3] in this study, PE values have been found to be 0.188-0.629 [29] and 0.175-0.552 [3] for Gry and Yugoslav Pied cattle, respectively. The total PE values were 0.979 [29] and 0.996 [3] . The total PE values were estimated for Holstein-Friesian, Brown Swiss ÖZŞENSOY, KURAR, DOĞAN, BULUT NİZAMLIOĞLU, IŞIK, ÇAMLIDAĞ, ALTUNOK and their crosses with native cattle breeds in Turkey [30] and found to be similar (>0.9999) with this study.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…By using the same 7 [29] and 11 markers [3] in this study, PE values have been found to be 0.188-0.629 [29] and 0.175-0.552 [3] for Gry and Yugoslav Pied cattle, respectively. The total PE values were 0.979 [29] and 0.996 [3] . The total PE values were estimated for Holstein-Friesian, Brown Swiss ÖZŞENSOY, KURAR, DOĞAN, BULUT NİZAMLIOĞLU, IŞIK, ÇAMLIDAĞ, ALTUNOK and their crosses with native cattle breeds in Turkey [30] and found to be similar (>0.9999) with this study.…”
Section: Discussionmentioning
confidence: 82%
“…Comparing with other marker systems, microsatellites [1] , exist widely in the genome, have features of higher polymorphism and codominant inheritance [2] . Due to their high polymorphism and technical ease including suitability for PCR technology and capillary electrophoresis, microsatellites are widely preferred in the paternity testing efforts of various mammalian species [3] . Correct determination of genetic relationships among animal populations has critical importance for development of selection programs [3] , generation of pedigree structures [4] , estimation of heritability [5,6] , and breeding values [7] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Short tandem repeats (STRs, microsatellites) have been the recent and internationally preferred molecular markers to trace studbook information from the species down to the individual level in all types of organisms ranging from lianas (Lacombe et al, 2013) to fish (Liu et al, 2012), insects (Wong et al, 2012), birds (Hadfield et al, 2006;Guerier et al, 2012), and mammals (Cutullé et al, 2010;Stevanovic et al, 2010;Souza et al, 2012). Microsatellites with a high level of heterozygosity are relatively more powerful in assigning relatedness per locus than those with a low level of heterozygosity.…”
Section: Introductionmentioning
confidence: 99%